Regulation of antifreeze polypeptide biosynthesis in the winter flounder (Pseudopleuronectes americanus) - Fourney, Ronald Mitchell (Memorial University of Newfoundland, 1984)
The heterogeneity of antifreeze polypeptides (AFP) in the Newfoundland winter flounder Pseudopleuronectes americanus was analyzed by reverse phase high performance liquid chromatography (HPLC) and by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Seven AFP components could be readily, resolved. Five of the components were similar in molecular weight (3,300) and amino acid composition. Two of the AFP components were larger (4,500) and contained valine. The two major components (components 6 and 8) were identical to those reported earlier from our laboratories (Davies et al., Proc. Natl. Acad. Sci., USA 79, 335, 1982). -- Serum AFP were isolated from winter flounder collected from Nova Scotia, New Brunswick and Long Island (New York) and compared to the AFP found in Newfoundland winter flounder. These peptides were analysed by reverse phase HPLC, and showed nearly identical elution profiles to that of Newfoundland AFP. Individual components from New Brunswick and Long Island had antifreeze activity and agreed with the activity measurements previously established for the Newfoundland AFP. Amino acid analyses of the major AFP components from the different flounder populations indicated that they had similar compositions. A minor variation which included valine in one AFP component was noted in the New Brunswick sample suggesting that a limited amount of genetic polymorphism may be present in the winter flounder population from New Brunswick. In general, there appears to be little or no variation in the structure of the AFP from winter flounder inhabiting different geographical habitats. In view of the similarity of the serum AFP components and in light of recent information on the structure and genomic organization of AFP genes, it is likely that the winter flounder AFP components are products of an AFP gene family. -- The seasonal synthesis of AFP in winter flounder is influenced by photoperiod and comes under the control of the pituitary gland. The effects of hypophysectomy (hypex) and long day length ...